2021
DOI: 10.1186/s12884-021-03872-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Mothers’ experiences of caring for preterm babies at home: qualitative insights from an urban setting in a middle-income country

Abstract: Background Preterm delivery is the birth of a baby before 37 weeks of gestation. This global phenomenon is a critical issue of concern especially in developing countries that are resource-constrained when it comes to the management of preterm babies. Complications associated with prematurity contribute significantly to under-five mortality and are linked with feelings of despair, grief, and anxiety among mothers. Methods This was a qualitative desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
5
7
0
Order By: Relevance
“…Like Garti et al (2021), we found that mothers were comforted and encouraged by family members, friends, religion and health professionals and confirm the quest by health professionals to have psychologists complement neonatal care teams and to set up support groups in hospitals and communities. However, in the absence of psychologists, nurses and midwives trained in family systems care (FSC), a care approach where families and healthcare providers are seen as mutually beneficial partners revolving on principles of dignity and respect, information sharing, participation, and collaboration (WHO, 2019) can establish therapeutic relationships with families along the CoC (Wright & Bell, 2021;Wright & Leahey, 2013).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Like Garti et al (2021), we found that mothers were comforted and encouraged by family members, friends, religion and health professionals and confirm the quest by health professionals to have psychologists complement neonatal care teams and to set up support groups in hospitals and communities. However, in the absence of psychologists, nurses and midwives trained in family systems care (FSC), a care approach where families and healthcare providers are seen as mutually beneficial partners revolving on principles of dignity and respect, information sharing, participation, and collaboration (WHO, 2019) can establish therapeutic relationships with families along the CoC (Wright & Bell, 2021;Wright & Leahey, 2013).…”
Section: Discussionsupporting
confidence: 67%
“…Studies have widely discussed the psychosocial traumas faced by mothers whose babies were admitted in neonatal wards (Al Maghaireh et al, 2016;Garti et al, 2021). The risk of neglect due to stigma and shame have been well established (Sakyi et al, 2020;Smith et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it has been documented that parents were anxious about mastering baby care during discharge, and gradually developed confidence through the implementation of the home care program 48 . Mothers who have limited access to counseling and support services are more likely to engage in inadequate coping, especially if they are ill‐informed and unable to discern between their preterm babies' immediate and ongoing needs 49 . Health professionals can ensure a smooth transition from hospital to home by enhancing the parents' knowledge and skills in preterm baby care, taking into the account personal circumstances and practical needs and preparing them for discharge 50 …”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women's anemia is a major global health problem that influences both the development of the fetus and the health of the mother [ 1 ]. Preterm delivery is one of the major challenges of pregnancy and is often related to circumstances about the health of the mother [ 2 ]. Maternal anemia and preterm deliveries have been linked; this association has been studied extensively since it has significant consequences for prenatal care and newborn outcomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%